Not your father's palliative care - Susan M. Walsh, DPM, MBA (Foot & Ankle Surgery: Techniques, Reports & Cases)
The specialty and prevalence of palliative care has substantially grown in the past two decades, such that multiple professional organizations are addressing the topic as it uniquely influences their providers and patient populations. A 66 year old female with a bimalleolar ankle fracture in the setting of multiple comorbid conditions provides an example of the need for including the principles of palliative medicine in the care of those patients with foot and ankle pathology.